The Development of Advance Organizer Based Distance Learning in Chemistry Bonding Material - Widyastuti, Niken; Riswandi, Riswandi; Fitriawan, Helmy (Journal of Education Technology, 2021)
The spread of the Covid-19 virus requires the government to take a policy of organizing education online. Learning chemical bonding material is strived to be developed according to students' needs and learning objectives reflected in the curriculum. This study aims to develop advance organizer-based distance learning on chemical bonding material and measure the effectiveness of this product. This study uses the Dick and Carey development model approach. The test subjects in this study were 39 students in class X students of laboratory testing analysis competency for the 2020/2021 academic year. The instruments used included assessment questionnaires, observations, interviews, validation sheets, and students' cognitive knowledge tests. The data obtained were analyzed using quantitative descriptive statistics and data on the effectiveness of learning using an n-gain score. This study obtained online learning products with an average validation score of 3.51 on a scale of 4.00, and the student gain value before and after using advance organizer-based online learning was 0.52. This research concludes that advanced organizer-based online learning products on chemical bonding material are very feasible and practical. These findings will be an input for developing chemical bonding materials and research the development of chemistry learning during a pandemic.